Synthesis and anti-fungal effect of silver nanoparticles-chitosan composite particles - Huang, Keng-Shiang; Wang, Lung-Shuo; Wang, Chih-Yu; Yang, Chih-Hui; Hsieh, Chen-Ling; Chen, Szu-Yu; Shen, Chi-Yen; Wang, Jia-Jung (International journal of nanomedicine, 2015)
Silver nanoparticles have been used in various fields, and several synthesis processes have been developed. The stability and dispersion of the synthesized nanoparticles is vital. The present article describes a novel approach for one-step synthesis of silver nanoparticles-embedded chitosan particles. The proposed approach was applied to simultaneously obtain and stabilize silver nanoparticles in a chitosan polymer matrix in-situ. The diameter of the synthesized chitosan composite particles ranged from 1.7 mm to 2.5 mm, and the embedded silver nanoparticles were measured to be 15 ± 3.3 nm. Further, the analyses of ultraviolet-visible spectroscopy, energy dispersive spectroscopy, and X-ray diffraction were employed to characterize the prepared composites. The results show that the silver nanoparticles were distributed over the surface and interior of the chitosan spheres. The fabricated spheres had macroporous property, and could be used for many applications such as fungicidal agents in the future.